Polyamine Metabolism Promotes the Progression of Thyroid Carcinoma by Regulating the Immune Phenotype of Tumor Associated Macrophages - Haoran Ding; Lingling Xue; Shaoshi Zhu; Ziyu Wang; Huan Gui; Guang Zhang; Ning Tang; Haozhen Ren; Dayu Chen (Smart Medicine)
ABSTRACT Polyamine metabolism is a key regulator of cellular proliferation and immune modulation, and its dysregulation is implicated in multiple carcinoma pathogenesis. Macrophages also greatly influence tumor progression by regulating the immune microenvironment. However, the role of polyamine metabolism in thyroid cancer macrophages remains understudied. This study explores the connection between polyamine metabolism and macrophages in thyroid cancer. Using the THCA dataset gene expression analysis and single‐cell data, we identified macrophage subpopulations. We assessed immune scores, matrix scores, immune checkpoint scores, and immune cell types using Bulk‐RNA data and the TIDE platform to predict immune checkpoint inhibitor responses. Clinical specimens validated our findings. Our results show a significant association between polyamine metabolism and the clinical and biological characteristics of thyroid cancer, including macrophage trajectory. Notably, macrophage subpopulations affected by polyamine metabolism have strong prognostic value, especially in immunotherapy patients. We found that changes in these subpopulations correlate with thyroid cancer development, and tumor tissue can regulate macrophage polyamine metabolism. This study provides new insights into how polyamine metabolism affects macrophages and the tumor microenvironment, influencing tumor growth and anti‐tumor immune responses in thyroid cancer.